Erratum to: Leptogenesis in the Neutrino Option - I. Brivio; K. Moffat; S. Pascoli; S. T. Petcov; J. Turner (Journal of High Energy Physics, 2020)
The related work by Vedran Brdar, Alexander J. Helmboldt, Sho Iwamoto and Kai Schmitz.